Desenvolvimento de um imunossensor descartável acoplado a um sistema microfluídico para determinação de um biomarcador tumoral - Peverari, Camila Rizzardi (2016)
Breast cancer is the most common type of cancer among women and results in 70% of cases of estrogen receptor alpha (ERα) overexpression, a tumor biomarker. In the present study we developed a sensitive and low cost disposable electrochemical immunosensor, coupled with a microfluidic system, as an alternative to determine ERα, since there are no reports on the determination of this compound in the literature using this method. The immunosensor was developed by the screen printing method, comprising a reference electrode, a counter electrode and an array of eight working electrodes, all disposable. The working electrodes were modified by layer-by-layer with poly(diallyldimethylammonium chloride) (PDDA) and gold nanoparticles decorated with glutathione (AuNP-GSH), in order to support, by covalent bond, a double-stranded DNA containing an estrogen response element (dsDNA-ERE). Also, we use magnetic particles containing thousands of antibodies and enzymes, wherein the enzymes are responsible for indirect response from the immunosensor and antibodies are used to capture the analyte in the sample. Once that the analyte is captured, it interacts with the dsDNA-ERE immobilized on the surface of the working electrode. In the linear range 16.6 to 513.3 fg mL-1 were obtained detection limit of 10.0 fg mL-1, quantification limit of 16.89 fg mL-1 and a sensitivity of 7.7 nA mL fg [ ERα]-1. Finally, it was possible to test the immunosensor front of a real sample lysate cells MCF-7, which showed that the device is a promising choice for use in the treatment and possible early diagnosis of breast cancer.